Study on Mechanical Properties of TMT Bars Manufactured in Nepal - Yadav, Umesh; Ale, Bhakta Bahadur (Journal of Advanced College of Engineering and Management, 2021)
Three grades of deformed steel bar are presently available in Nepal for concrete reinforcement. The deformed bars are graded according to their specified yield strength. These are Fe415, Fe500 and Fe500D. CTD bars of grade more than Fe415 are scarcely available in market. However, TMT bars of Fe500 grade are easily available in market. This study is undertaken to evaluate the variability of the mechanical properties of reinforcing steel granted with NS Mark and to analyze the degree to which these rolling mills satisfy the minimum requirements established by product national standard NS:191. The data obtained from test results are statistically analyzed to evaluate the variability in the mechanical properties of TMT bars. For the tested mechanical properties, the parameters evaluated for each bar size, and grade at confidence level at 95 % are mean, standard deviation, coefficient of variation, minimum, maximum, skewness. The samples were collected from NBSM reference sample store room of FY 2073-74 and FY 2074-75. These samples were from nineteen industries and twenty-two different brands. Total 745 numbers of TMT bars of grade Fe500 and Fe500D were tested at NBSM mechanical testing laboratory. The mechanical properties determined from the tested samples are: mass per meter run, yield stress, tensile stress, percentage elongation, UTS/YS ratio, total elongation at maximum force, and bond value.The tested data and obtained statistics of different mechanical properties for the separate and combined data takes on an important practical significance and may be used in calibrating local specifications and designs.